DAMPAK MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KETERBUKAAN SISTEM PENGENDALIAN INTERNAL PADA PERUSAHAAN PERBANKAN - Finanda Salsahira; Wahyu Helmy Dimayanti Sukiswo (RISTANSI: Riset Akuntansi, 2025)
This study aims to evaluate the impact of ownership structure, board independence, and the presence of an audit committee on the transparency of internal control disclosures in the banking sector. A qualitative approach was employed through a literature review, analyzing ten selected articles sourced from Google Scholar. The findings indicate that institutional ownership, board independence, and the effectiveness of the audit committee significantly influence internal control disclosures. High institutional ownership enhances accountability and transparency, whereas concentrated ownership tends to limit disclosure due to its focus on short-term interests. An independent board of commissioners promotes more objective oversight and encourages information transparency, while a lack of independence may lead to conflicts of interest that hinder effective decision-making. An audit committee that performs its duties effectively contributes to stronger internal control oversight, while an ineffective committee may weaken transparency due to insufficient monitoring.